Website-Based Blended Learning as an Innovation in Mathematics Learning to Improve Students' Mathematical Representation Skills - Muhammad Ridho Danu Muslikhan; Fitri Umardiyah (APPLICATION: Applied science in Learning Research, 2026)
Mathematical representation ability is an important competency in mathematics learning because it allows students to present, interpret, and communicate mathematical concepts through visual, symbolic, and verbal representations. However, this ability is still relatively low due to learning that tends to be teacher-centered and does not utilize technology. This study aims to determine the effect of a blended learning model assisted by a Google Sites-based website on students' mathematical representation ability on similarity and congruence material. The study used a quantitative approach with a pre-experimental method through a One Group Pretest-Posttest design on 21 ninth-grade students of MTs Al-Ihsan Kalikejambon, Tembelang, Jombang. Data were collected using pretest and posttest tests, observation sheets, and documentation, then analyzed using the Shapiro-Wilk normality test and Paired Sample t-Test. The results showed an increase in the average value from 53.29 to 90.14, with a significance value of 0.000 (<0.05), so the alternative hypothesis was accepted. These findings indicate that integrating face-to-face instruction with web-based learning through Google Sites provides an effective learning environment that enhances students' conceptual understanding and mathematical representation skills